A SOLUTION AND MAINTENANCE OF PERI-IMPLANT PROBLEM; CASE REPORT FOR 5 YEARS PERI-IMPLANT TISSUE - Chang Kyu Lee (Faculty of Dentistry, Universitas Indonesia, 2015)
The overall objective of this study is to evaluate the long term results of interpositional connective tissue graft and horizontal and vertical bone augmentation in recessed area of interproximal papilla. Atrophic ridges rebuilt through GBR procedures. For this study, 2 major alterations are made in the surgical technique describes. First, the horizontal and vertical bone augmentation graft is obtained from autograft like ascending ramus or allograft with or without platelet-rich plasma and barrier membrane. Second, connective tissue for interpositional grafting is obtained from hard palate. This interpositioning graft would be success by use of pouch technique or envelope flap technique. From 1998, among over than 120 patients of implant treated. for this study, regardless of 1-staged or 2-staged surgery or type of implant surface treated, 60 implants of 18 patients which has a dissatisfaction on anterior region, food impaction on posterior region subjectively, or has a black-triangle on anterior and flattened inter-implant spaces clinically was selected. Differences of success rate between inter-dental and inter-implants depend on blood supply and distance between implants. Autografts, PRP and anorganic bovine bone Bio-Oss have been successfully employed for isolated augmentation area. It is essential to make the CT graft neovascularize to a recipient site, overcorrection of graft, immobilization of graft and tension-free suture. Based on annual measurements of gross texture, pocket probing depth, attachment level, and width of keratinized mucosa, this 5-year study indicates that interpositional CT graft when used in conjunction with appropriate bone augmentation technique, can become successfully esthetics and yield predictable maintenance results.